Study on The Thermal Distortion, Hardness and Microstructure of St 37 Steel Plate Joined Using FCAW - Maijuansyah Maijuansyah; Yanuar Rohmat Aji Pradana; Gaguk Jatisukamto; Solichin Solichin (Universitas Negeri Malang, 2019)
This study sets out to investigate the distortion angle, microstructure, and hardness of St 37 steel plate weld joint produced by FCAW using the welding current of 80, 110, and 140 A. By using flat position, CO2 and E71T-1 wire were utilized as a shielding gas and electrode filler, respectively. The distortion angle measurement was done on 3 different locations of the welded sample perpendicular to weld direction by using bevel protractor. The micro Vickers tests were then applied gradually at the cross-sectional surface with a distance of 0, 5, 10 and 15 mm from weld centreline using the load of 300 g for indentation time of 15 s. A series of microstructural observations were subsequently directed on cross-sectional weld joint regions including base metal, heat-affected zone (HAZ) and weld metal to investigate the microstructural transformation. From the results, it can be observed that increasing welding current can reduce the hardness at all indentation regions as well as inducing a higher level of thermal distortion occurred on a weld joint, especially at HAZ. The microstructural transformation was also observed at sample welded using various welding current. Both heat input and cooling rate subjected to the welded sample played an important role to characterize their properties.